Teaching research in paediatrics: A "hands on" experience for medical students - Aggarwal, S.; Chadha, P.; Kalia, S.; Richardson, S.; Winterbottom, L.; Shields, Linda (ANZAME: The Association for Health Professional Education, 2009)
Aim: To teach medical students about the methods, ethics and practicalities of conducting social science research, using a "hands on" approach. Methods: For a Student Selected Component (elective) offered by the Hull York Medical School, five students, under supervision, conducted a pilot study of a research project about family-centred care in three children's hospitals in the UK. They used a set of questionnaires for parents of hospitalised children, and staff, developed in Australia. Results: The students all scored highly on assessment and demonstrated that they had learned much about research methods and the ethics surrounding data collection with families in a hospital setting. The results confirmed the reliability of the tool for use in the UK. Conclusions: The students learned about social science research, its methods, ethical issues and practical problems surrounding data collection.